International Comparative Study of Statistics Learning Trajectories Based on PISA Data on Cognitive Diagnostic Models - Jia, Bing; Zhu, Zhemin; Gao, Hang (Frontiers in Psychology, 2021)
The cognitive diagnosis model is an emerging evaluation theory. Students' mastery of fine-grained knowledge points can be obtained via the Cognitive Diagnostic Model (CDM), which can subsequently describe the learning trajectory. The latter is a description of the student's learning progress in a specific area, through which teaching and learning can be linked. This research is based on 9 statistical items in PISA 2012 and an analysis of the response data of 30,092 students from 14 countries from four attributes based on CDM. Then, it obtains the students' learning trajectory in statistical knowledge. The study found that Bulgaria, Costa Rica, and Peru have the same learning trajectories. Mexico and Serbia have the same learning trajectories. The learning trajectories of most of the 14 countries are as follows: 1.) uncertainty, 2.) data handling, 3.) a statistical chart, and 4.) average.